PENGARUH PENILAIAN BERBASIS KELAS TERHADAP HASIL BELAJAR SISWA DI KELAS X.1 PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM SMA NEGERI 1 KUANTAN MUDIK - Marlina Marlina; Bustanur Bustanur; Zulhaini Zulhaini (Universitas Islam Kuantan Singingi, 2020)
According to the title, this research was held at SMA Negeri 1 Kuantan mudik. To facilitate the research, the problem was formulated, namely, the role of the teacher in the assessment, the factors that influence the assessment and the effect of class-based assessment on student learning outcomes in PAI subjects in SMA Negeri 1 Kuantan mudik.